Anti-TNFα Treatment After Surgical Resection for Crohn's Disease Is Effective Despite Previous Pharmacodynamic Failure. Issue 5 (22nd February 2017) - Assa, Amit; Bronsky, Jiri; Kolho, Kaija-Leena; Zarubova, Kristyna; de Meij, Tim; Ledder, Oren; Sladek, Margaret; van Biervliet, Stephanie; Strisciuglio, Caterina; Shamir, Raanan
Abstract : Background: The outcome of patients with Crohn's disease who failed anti-tumor necrosis factor alpha (anti-TNFα) therapy despite adequate serum drug levels (pharmacodynamic failure) is unclear. We aimed to assess such pediatric patients who underwent intestinal resection and were re-treated with the same anti-TNFα agent postoperatively. Methods: Pediatric patients with Crohn's disease who underwent intestinal resection and were treated with anti-TNFα agents postoperatively were assessed retrospectively. Patients were stratified to those with preoperative anti-TNFα pharmacodynamic failure and those with no preoperative anti-TNFα treatment. Results: A total of 53 children were included, 18 with pharmacodynamic failure and 35 controls. Median age at intestinal resection was 14.8 years with 23 (43%) girls. The median time from intestinal resection to anti-TNFα initiation was 8 months (interquartile range 4–14 months). At the time of postoperative anti-TNFα initiation there were no differences in clinical, laboratory, and anthropometric measures between groups. Similar proportions of patients from both groups were in clinical remission on anti-TNFα treatment after 12 months and at the end of follow-up (1.8 years, interquartile range, 1–2.9 years): 89% versus 88.5% and 83% versus 80% for pharmacodynamic failure patients and controls, respectively; P = 0.9. No significant differences were observed at 14 weeks and 12 months of postoperative anti-TNFα treatment including endoscopic remission rate and fecal calprotectin. Both groups significantly improved all measures during postoperative anti-TNFα treatment. Conclusions: Pediatric patients with Crohn's disease who failed anti-TNFα therapy despite adequate drug levels and underwent intestinal resection can be re-treated with the same agent for postoperative recurrence with high success rate similar to that of anti-TNFα naive patients.